Laboratory preparation methods for human-derived fecal microbial suspensions for fecal microbiota transplantation: a review and standardization perspectives - Gong, Jinhua; Liu, Yuchi; Huang, Liuye (Frontiers in Microbiology, 2025)
Fecal microbiota transplantation (FMT) has advanced significantly as a therapeutic approach over the past few decades. Preparing fecal suspensions for FMT is one of the key steps. However, there is no unified standard or recognized procedure for preparing fecal suspensions in laboratories. This review evaluated the steps currently employed in laboratories to prepare fecal suspensions for FMT, including sample collection, suspension buffers, homogenization, purification, filtration, centrifugation, cryopreservation, dosage, the operating environment, and the transplantation form. This review focuses on the different operations of each preparation step, aiming to provide a reference for the laboratory preparation of fecal suspensions.